The Implementation of Curriculum During Covid-19 Pandemic in English Teaching - Nikmah, Alfu; Fitriani, Aulia (Lembaga Pendidikan Hikmatun Najah Blora, 2023)
This study promotes the description of the English learning and teaching during Covid break. The objective of the study is to find out the implementation of English teaching and learning during covid in MAN 2 Kudus. The qualitative research is employed in this study. The participants involve the English teachers of MAN 2 Kudus. The result of the study revealed that there are some changes of the implementation of teaching and learning during Covid. The online teaching and learning becomes an solution during covid. Teacher used some platform of social media in teaching. They are youtube, Whats app, E learning Kemenag. The students were active in the learning by presentation and also discussion. It was challenging situation that made the different situation compared before Covid break. The innovation and creative teaching really needed to assist students to stay focus in the far distance learning.